A new physiological medium uncovers biochemical and cellular alterations in Lesch-Nyhan disease fibroblasts - Paula Escudero-Ferruz; Neus Ontiveros; Claudia Cano-Estrada; Diane J. Sutcliffe; H. A. Jinnah; Rosa J. Torres; José M. López (BMC, 2024)
Abstract Background Lesch-Nyhan disease (LND) is a severe neurological disorder caused by the genetic deficiency of hypoxanthine-guanine phosphoribosyltransferase (HGprt), an enzyme involved in the salvage synthesis of purines. To compensate this deficiency, there is an acceleration of the de novo purine biosynthetic pathway. Most studies have failed to find any consistent abnormalities of purine nucleotides in cultured cells obtained from the patients. Recently, it has been shown that 5-aminoimidazole-4-carboxamide riboside 5ʹ-monophosphate (ZMP), an intermediate of the de novo pathway, accumulates in LND fibroblasts maintained with RPMI containing physiological levels (25 nM) of folic acid (FA), which strongly differs from FA levels of regular cell culture media (2200 nM). However, RPMI and other standard media contain non-physiological levels of many nutrients, having a great impact in cell metabolism that does not precisely recapitulate the in vivo behavior of cells. Methods We prepared a new culture medium containing physiological levels of all nutrients, including vitamins (Plasmax-PV), to study the potential alterations of LND fibroblasts that may have been masked by the usage of non-physiological media. We quantified ZMP accumulation under different culture conditions and evaluated the activity of two known ZMP-target proteins (AMPK and ADSL), the mRNA expression of the folate carrier SLC19A1, possible mitochondrial alterations and functional consequences in LND fibroblasts. Results LND fibroblasts maintained with Plasmax-PV show metabolic adaptations such a higher glycolytic capacity, increased expression of the folate carrier SCL19A1, and functional alterations such a decreased mitochondrial potential and reduced cell migration compared to controls. These alterations can be reverted with high levels of folic acid, suggesting that folic acid supplements might be a potential treatment for LND. Conclusions A complete physiological cell culture medium reveals new alterations in Lesch-Nyhan disease. This work emphasizes the importance of using physiological cell culture conditions when studying a metabolic disorder.